PENGARUH LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI PADA SISWA KELAS XI IIS DI SMA BAWARI PONTIANAK - Kamariyah, Tri Yatmi; Ulfah, Maria; Achmadi, Achmadi (Universitas Tanjungpura, 2022)
This study aims to determine the effect of the family environment on student achievementin economics class XI IIS at SMAS Bawari Pontianak. The method used in this research isdescriptive method. the form of the research, the form of research that is determined is thestudy of relationships (Interrelationship Studies). Data collection techniques are directcommunication techniques, indirect communication techniques and documentary studytechniques. Data collection tools are questionnaires, interviews and notes. 1) This researchis a population of 102 students of class XI IIS SMAS Bawari Pontianak. A sample of 50students consists of 3 classes. 2) The family environment of class XI IIS SMAS BawariPontianak 83.66% is categorized as very good. Student achievement in class XI ISS SMASBawari Pontianak is the highest class XI IIS 1 followed by class XI IIS 2 and the last isclass XI IIS 3. 3) There is an influence of family environment on student achievement inclass XI ISS SMAS Bawawi Pontianak, the value of t_count is obtained =30.977 greaterthan the value of t_table = 2.010. 4) How much does the family environment affect studentachievement in class XI IIS SMAS Bawari Pontianak, namely Y= 31.13 + 0.530 XKeywords: Family Environment, Learning Achievement